Weight restoration on a high carbohydrate refeeding diet promotes rapid weight regain and hepatic lipid accumulation in female anorexic rats. Issue 1 (December 2016) - Giles, Erin; Hagman, Jennifer; Pan, Zhaoxing; MacLean, Paul; Higgins, Janine
Abstract Background There is currently no standard clinical refeeding diet for the treatment of anorexia nervosa (AN). To provide the most efficacious AN clinical care, it is necessary to define the metabolic effects of current refeeding diets. Methods An activity-based model of anorexia nervosa (AN) was used in female rats. AN was induced over 7d by timed access to low fat (LF) diet with free access to a running wheel. Plasma hormones/metabolites and body composition were assessed at baseline, AN diagnosis (day 0), and following 28d of refeeding on LF diet. Energy balance and expenditure were measured via continuous indirect calorimetry on days −3 to +3. Results AN induction caused stress as indicated by higher levels of corticosterone versus controls (p < 0.0001). The rate of weight gain during refeeding was higher in AN rats than controls (p = 0.0188), despite lower overall energy intake (p < 0.0001). This was possible due to lower total energy expenditure (TEE) at the time of AN diagnosis which remained significantly lower during the entire refeeding period, driven by markedly lower resting energy expenditure (REE). AN rats exhibited lower lipid accumulation in visceral adipose tissues (VAT) but much higher liver accumulation (62 % higher in AN than control;p < 0.05) while maintaining the same total body weight as controls. It is possible that liver lipid accumulation was caused by overfeeding of carbohydrate suggesting that a lower carbohydrate, higher fat diet may be beneficial during AN treatment. To test whether such a diet would be accepted clinically, we conducted a study in adolescent female AN patients which showed equivalent palatability and acceptability for LF and moderate fat diets. In addition, this diet was feasible to provide clinically during inpatient treatment in this population. Conclusion Refeeding a LF diet to restore body weight in female AN rats caused depressed TEE and REE which facilitated rapid regain. However, this weight gain was metabolically unhealthy as it resulted in elevated lipid accumulation in the liver. It is necessary to investigate the use of other diets, such as lower carbohydrate, moderate fat diets, in pre-clinical models to develop the optimal clinical refeeding diets for AN.